VD_FINDINFO Faillite / 2009 / 7 vom 26. Februar 2009 - VD Tribunal cantonal (2009)
PROCÉDURE DE FAILLITE, DÉCISION D'IRRECEVABILITÉ, POUVOIR DE REPRÉSENTATION | 458 al. 1 CPC, 174 al. 1 LP, 58 al. 1 LVLP